2023
DOI: 10.1080/0886022x.2022.2150217
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the EKFC equation for glomerular filtration rate estimation and comparison with the Asian-modified CKD-EPI equation in Chinese chronic kidney disease patients in an external study

Abstract: Objectives The aim of this study is to determine whether new European Kidney Function Consortium (EKFC) equation is more applicable than Asian-modified CKD-EPI equation in clinical practice, having a higher accuracy in estimating GFR in our external CKD population. Methods We calculated estimated GFR EKFC and GFR CKD-EPI independently using the EKFC and Asian-modified CKD-EPI formulas, respectively. The clinical diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…It should be noted that standardization of SCr is essential for accurate use of unbiased eGFR equations when these equations were developed using standardized SCr, as has recently been demonstrated [ 21 ]. Recently, it has been shown that the EKFC equation performs very well in populations other than White Europeans, notably in Black populations of Europe, Brazil, and Africa [ 22 ] and in the Korean and Chinese populations [ 23 - 25 ].…”
Section: Serum Creatininementioning
confidence: 99%
“…It should be noted that standardization of SCr is essential for accurate use of unbiased eGFR equations when these equations were developed using standardized SCr, as has recently been demonstrated [ 21 ]. Recently, it has been shown that the EKFC equation performs very well in populations other than White Europeans, notably in Black populations of Europe, Brazil, and Africa [ 22 ] and in the Korean and Chinese populations [ 23 - 25 ].…”
Section: Serum Creatininementioning
confidence: 99%
“…This decline in performance in the chronic kidney disease population was also described in the Asian population, where in the subgroup of patients with GFR<= 60 ml/min/1.73m2, P30 was 68.1%, while in the GFR > 60 ml/min/1.73 m2 group, P30 was 95.7%. Although overall, the performance of the EKFC equation remains acceptable [23], the results are not conclusive. Furthermore, P30s in both groups were lower when using creatinine as a biomarker.…”
Section: Discussionmentioning
confidence: 84%
“…Even though these newly proposed eGFR equations can be applied globally, their evaluation is mandatory before being adopted in regions other than North America or Europe, and is important, considering the conflicting recommendations on the new equations. Several studies have explored the performance of these new equations in Asian populations [18][19][20]; however, there has been only one large-scale study, and there has been no study conducted in the pediatric age group. Thus, it would be necessary to compare and verify the results of each equation in Asian populations including children, adolescent, and adults.…”
Section: Introductionmentioning
confidence: 99%